Microsoft 2.0: How Microsoft Plans to Stay Relevant in the Post-Gates Era - Jo Foley Mary (Wiley, 2008)
"The award-winning journalist author has access to inside information and what she has to reveal will bring tremendous media attention".(The Bookseller, Friday 14th March 2008)